Extending Computational Thinking: Embodied Learning Through Socioenactive Scenarios (Constructionism Conference Proceedings, 2025)
Although not always understood in the same way, the ideas of Computational Thinking have gained attention from policymakers in curriculum educational fields, particularly in primary math and K-12 education around the world, as necessary 21st-century skills to foster children’s competence in problem-solving. In this work we argue that since its reappearance, many transformations have happened in the computational and social contexts, which make us rethink the literacies regarding computer-based environments. In this paper we extend the idea of computational thinking with a socioenactive perspective to computing, which considers a tripartite coupling of the physical, the digital and the social dimensions of ubiquitous computing based environments. We illustrate aspects of a socioenactive computational thinking with an analysis of two different scenarios. Results point out some aspects to be resumed from the origins of constructionism (for example, project action and body syntonicity) and others to be included in the subject (for example, sense-making, body affectivity and intersubjectivity).